Decomposition efficiency and aerosol by-products of toluene, ethyl acetate and acetone using dielectric barrier discharge technique. (December 2019) - Yu, Huan; Hu, Wei; He, Jun; Ye, Zhaolian
Abstract: Dielectric barrier discharge (DBD) has been widely used as end-of-pipe technology to degrade low-concentration volatile organic compound (VOC) emissions. In this work, the influence of DBD conditions including discharge voltage, VOC residence time in DBD plasma, VOC initial concentration and synergistic effect of multiple VOC mixing on the decomposition efficiency of three VOCs (toluene, ethyl acetate and acetone) were investigated systematically. One focus of this work was to investigate size distribution and chemical composition of aerosol by-products. The results suggested that high discharge voltage, long residence time and low VOC initial concentration would increase VOC removal ratio and their conversion to CO2 . Among the three VOCs, toluene was easiest to form particles with a mode diameter between 40 and 100 nm and most difficult to be decomposed completely to CO2 . Maximum aerosol yield from toluene was observed to account for 13.1 ± 1.0% of initial concentration (400 ppm) in the condition of discharge voltage 6 kV and residence time 0.52 s. Gas chromatography-mass spectrometry analysis showed that non-nitrogen containing benzene derivatives, nitrophenol derivatives and amines were the main components of toluene aerosol by-products. For ethyl acetate and acetone, aerosols could only be produced in the condition of high discharge voltages (>7.5 kV) and long gas residence time (≥0.95 s) with a bimodal distribution below 20 nm. When the mixture of three VOCs was fed into the plasma, we observed a strong synergistic effect that led to higher VOC removal ratio, but lower conversion of decomposed VOCs to CO2 and aerosols. Highlights: Effects of discharge voltage, residence time and concentration were investigated. Synergistic effect removes more VOCs, but converts less to CO2 and aerosols. 14 compounds were identified by GC-MS in toluene aerosol by-products. Toluene is easier to form particles but more difficult to be converted to CO2 . The effect of residence time on aerosol yield is different for three VOCs.